2000
DOI: 10.1271/bbb.64.592
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Spontaneous High Expression of Heat Shock Protein 70 in Developing Zebrafish (Danio rerio)

Abstract: A spontaneous high expression of heat shock protein 70 (HSP 70) was detected in zebrafish (Danio rerio) at early larval stage (84 h after fertilization), but the HSP 70 level was either low or barely detectable in 12, 24, 36, 60, and 108 h after fertilization. The extracts of zebrafish at 80 and 84 h after fertilization formed a clear protein-DNA complex with a probe containing heat shock elements (HSEs), suggesting that this spontaneous expression of HSP 70 may be turned on via the binding of stage-specific H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Although the expression pattern of the 62-kDa factor seemed to correlate with the fluctuation in HSP 70 synthesis in developing zebrafish, the level of the HSF-1-like factor was barely detectable in 72-hr-old larvae in which the spontaneous HSP 70 synthesis was already in progress. As described in our previous report (Yeh and Hsu, 2000), the extracts of heattreated 80-hr-old larvae bound more strongly to the HSE probe than those of stressed zebrafish at other stages. When anti-HSF-1 antibodies (1:10 dilution) were added to the gel shift mixture with stressed zebrafish extracts included, an effective supershifting of the HSE-binding complex was observed.…”
Section: Hsf-1-independent Binding Of Unstressed Zebrafish Extracts Tsupporting
confidence: 76%
See 2 more Smart Citations
“…Although the expression pattern of the 62-kDa factor seemed to correlate with the fluctuation in HSP 70 synthesis in developing zebrafish, the level of the HSF-1-like factor was barely detectable in 72-hr-old larvae in which the spontaneous HSP 70 synthesis was already in progress. As described in our previous report (Yeh and Hsu, 2000), the extracts of heattreated 80-hr-old larvae bound more strongly to the HSE probe than those of stressed zebrafish at other stages. When anti-HSF-1 antibodies (1:10 dilution) were added to the gel shift mixture with stressed zebrafish extracts included, an effective supershifting of the HSE-binding complex was observed.…”
Section: Hsf-1-independent Binding Of Unstressed Zebrafish Extracts Tsupporting
confidence: 76%
“…In our previous study, a spontaneous high expression of HSP 70 was repeatedly detected in 84-hr-old zebrafish larvae, and the level of HSP 70 was either very low or barely detectable in zebrafish at other developmental stages, but coomassie blue-stained protein profiles for the extracts of unstressed zebrafish were very similar (Yeh and Hsu, 2000). Immunoblot analysis in this study clearly demonstrated the kinetics of the spontaneous HSP 70 expression during zebrafish development.…”
Section: Spontaneous and Heat-induced Hsp70 Expression In Developing supporting
confidence: 72%
See 1 more Smart Citation
“…Our heat shock-inducible Cre/Lox approach can lead to transgene expression in the absence of inducing stimuli, likely caused by the aberrant expression of the hsp70 promoter (18). However, other inducible approaches used to generate tumor models are also leaky.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, untreated hsp70-Cre embryos expressed 2.9 Ϯ 2.0% of the Cre transcript levels compared with siblings heat shocked for 1 h (n ϭ 4; heat shock from 24-25 hpf at 37°C and assessed for Cre expression at 28 hpf). Thus, the hsp70 promoter can be induced by heat shock treatment; however, the promoter is active at low levels during development even in the absence of heat shock (18,19).…”
Section: Human Krasg12d Expression Can Be Induced In Transgenic Zebramentioning
confidence: 99%